2015
DOI: 10.1111/trf.13270
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion‐induced alloimmunization and platelet refractoriness in a mouse model: mechanisms and interventions

Abstract: Together these findings introduce new experimental methods, basic mechanistic understanding, and a potential therapeutic intervention for alloimmunization to MHC-based antigens on transfused PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
2
25
0
5
Order By: Relevance
“…While leukoreduction has reduced the rates of alloimmunization and the levels of alloantibodies in those who do become alloimmunized, a significant risk of alloimmunization remains. Administration of CTLA4‐Ig to block costimulation has been shown to be effective at preventing alloimmunization to PLT transfusion in mice, but administration of such a broad immunosuppressive drug to transfusion recipients in a clinical setting introduces tremendous risks as transfusion recipients are often at increased risk of infection already. One advantage of using PRT to prevent alloimmunization is that the blood product itself is being treated, not the patient, making it a more targeted approach.…”
Section: Discussionmentioning
confidence: 99%
“…While leukoreduction has reduced the rates of alloimmunization and the levels of alloantibodies in those who do become alloimmunized, a significant risk of alloimmunization remains. Administration of CTLA4‐Ig to block costimulation has been shown to be effective at preventing alloimmunization to PLT transfusion in mice, but administration of such a broad immunosuppressive drug to transfusion recipients in a clinical setting introduces tremendous risks as transfusion recipients are often at increased risk of infection already. One advantage of using PRT to prevent alloimmunization is that the blood product itself is being treated, not the patient, making it a more targeted approach.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown the importance of CD4 1 T cells, the CTL-associated protein 4 axis, the splenic microenvironment, and complement receptors in inducing transfusion-associated platelet refractoriness. [7][8][9] These reports set the stage for the current study where Arthur et al immunize recipient mice with donor blood cells from a strain of mice that differ in MHC antigens. They find that mice with an intact immune system clear only the platelets from the MHC-mismatched mice, and not their own platelets.…”
Section: John P Manis and Leslie E Silberstein Harvard Medical Schoolmentioning
confidence: 99%
“…Трансфузії КТ хоч і є важливою лікувальною процедурою, але вони можуть викликати цілу низку побічних ефектів у реципієнта [6,13,16,29]. Ускладнення, які пов'язані з трансфузією КТ, визначаються переважно методом отримання концентрату, присутністю у ньому інших клітин, особливо лімфоцитів, неправильним підбором і обстеженням донора, дотриманням умов зберігання тощо.…”
unclassified
“…У разі появи дрібних точкових геморагій на верхній половині тулуба, крововиливів у кон'юнктиву та на сітківці ока, локальних кровотеч (травний тракт, матка, нирки, сечовий міхур тощо) необхідна трансфузія КТ за життєвими показниками [1,7,11]. Трансфузія КТ не показана при підвищеному руйнуванні тромбоцитів імунного ґенезу [4,9,22,29].…”
unclassified